Comparison of the covid-19 pandemic with the war paradigm - Šteiner, Alojz (Anali PAZU HD, 2022)
Year 2020, and as it appears 2021, will remain marked by the Covid-19 pandemic. It is a disease, not a war, but as a research challenge, the question arises, whether a pandemic can and should be compared to the war paradigm and its defensive-military implications, and to look for points of contact with the modern civilizational challenges of both. The war paradigm has transformed completely with the transition to a new millennium and before that with the collapse of bipolarity and the block division of the world. The emergence of hybrid warfare has changed the paradigm of war in the last decade to be indisclosable, and at the same time brought it very close to some of the implications that arise with the Covida-19 pandemic. Successful cope of pandemic it requires the best crisis management, such as with the emergence of war, which we want to fight effectively. This is also the core of understanding and views of how the pandemic is managed. In addition to confronting the pandemic and the covid-19 disease, we face an infodemia and the challenge of managing fear and obedience.
Keywords: covid-19; pandemic; epidemic; infodemia; war paradigm; hybrid war; ransformation; society resilience; crisis management